Pengaruh Struktur Organisasi , Kepemimpinan dan Kemampuan Sumber Daya Manusia terhadap Efektifitas Pelayanan Persertifikatan Hak Atas Tanah pada Kantor Pertanahan Kota Payakumbuh - Rahmad, Rahmad; Rahmawaty, Dian; Nurfitriyenny, Nurfitriyenny (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2022)
This study aims to reveal: To determine the influence of organizational structure (X1) on the effectiveness of land rights certification services (Y) at the Payakumbuh City Land Office, To determine the influence of leadership (X2) on the effectiveness of land rights certification services (Y) at the Land Office City of Payakumbuh, to determine the influence of HR capabilities (X3) on the effectiveness of land rights certification services (Y) at the Payakumbuh City Land Office and to determine together the influence of organizational structure, leadership and HR capabilities on the effectiveness of land rights certification services at the Office Land of Payakumbuh City. The population in this study was 35 respondents who were directed at the Payakumbuh City Land Office Employees The analytical tool used is Multiple Linear Regression using the SPSS program. The findings of this study are: 1) There is an influence between organizational structure and service effectiveness, there is a significant relationship between organizational structure and service effectiveness at the Land Office of Payakumbuh City 2) There is an influence of leadership on service effectiveness, there is a significant influence between leadership and service effectiveness at the office Land of Payakumbuh City.3) there is influence between HR capability and service effectiveness and there is a significant influence between HR capability and service effectiveness at the Payakumbuh City Land Office.4). There is a joint influence of organizational structure, leadership and HR capabilities on the effectiveness of services at the Payakumbuh City Land Office.Keywords:Organizational structure, leadership, HR capabilities, service effectiveness